ABOUT THE HEAVY ELEMENTS ABUNDANCES IN THE ATMOSPHERES OF STARS WITH LOW METALLICITY - Gopka, V. F.; Yushchenko, A. V.; Mishenina, T. V.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2017)
We present results of preliminary determinations of abundances of heavy elements in three metal-poor stars: HD37828, HD44008, HD221170. Careful comparison of observed and synthetic spectra permit us to increase the number of lines heavy elements identified in observed spectra. Results will be used for determinations of the abundances of these elements with the spectrum synthesis method in these and other metal-poor stars.